2021
DOI: 10.1016/j.ekir.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Involvement in Patients With Chronic Myelomonocytic Leukemia or BCR-ABL–Negative Myeloproliferative Neoplasms

Abstract: Introduction The identification of specific molecular signatures and the development of new targeted drugs have changed the paradigm of onco-nephrology, now allowing a multiscale approach of kidney involvement related to hematologic malignancies relying on combined hematologic and molecular assessments. In this study, we aimed to refine the spectrum of kidney disorders associated with chronic myelomonocytic leukemia (CMML) or BCR-ABL–negative myeloproliferative neoplasms (MPNs), 2 very rare condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(56 reference statements)
1
7
0
Order By: Relevance
“…However, Belliere et al. 13 identified a delay of 7.7 ± 2 years for CMML or BCR-ABL-negative myeloproliferative neoplasms patients. We found that lysozyme nephropathy and an infiltration by the CMML were by far the most frequent kidney diseases associated with CMML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Belliere et al. 13 identified a delay of 7.7 ± 2 years for CMML or BCR-ABL-negative myeloproliferative neoplasms patients. We found that lysozyme nephropathy and an infiltration by the CMML were by far the most frequent kidney diseases associated with CMML.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney injuries related to CMML were described in small cohorts, generally associated with myeloproliferative neoplasms. 13 , 14 There is a higher incidence of AKI (34.9%) and CKD (7.6%) among patients with myeloproliferative form of CMML. 8 Main findings revealed that tubulointerstitial compartment was the first kidney injury in a study of 8 CMML cases, with chronic tubulointerstitial nephropathy, and acute interstitial nephropathy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the present literatures, the other possible pathogenesis of PV associated with renal disease also include changing blood volume and viscosity which resulted in mesangial hypercellularity and matrix proliferation, vascular microthrombi, interstitium ischemia, and more rapid progression of renal failure. [ 27 , 28 ] However, according to the literature, the coexistence of the 2 diseases might be simply coincidental and no causative relationship is presented.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of impaired kidney function in our study remains unclear for most patients, but there are some indications in the literature which provide some possible explanations. In one study, 18 patients with myeloid neoplasms who were referred to a nephrology unit because of reduced renal function were retrospectively studied [ 28 ]. The study included 8 patients with CMML, 7 patients with essential thrombocytosis, 1 patient with polycythemia vera, and 2 patients with myelofibrosis.…”
Section: Discussionmentioning
confidence: 99%